Are Women Brave or Braver Than Men? Judgments of Implicit and Explicit Intergroup Comparisons - Lux, Alexandra; Bruckmüller, Susanne; Hoorens, Vera (Journal of Language and Social Psychology, 2023)
People learn about social groups by reading and hearing verbal statements. We investigated if the perceived truth and acceptability of such statements depend on whether they are implicitly vs. explicitly comparative (e.g., “Women are brave” vs. “Women are braver than men”). Participants (Study 1: Ns = 259; Study 2: N = 246) rated the truth, acceptability, familiarity, and positivity of implicitly vs. explicitly comparative, stereotypical vs. counter-stereotypical statements about positive vs. negative features. Consistent with an Etiquette Hypothesis, implicitly (vs. explicitly) comparative statements about positive features were judged as truer and more acceptable, presumably because they adhered better to a positivity norm. Consistent with a Fluency Hypothesis, stereotypical explicitly (vs. implicitly) comparative statements about age groups were judged as truer, presumably because of higher ease-of-processing. Thus, mechanisms affecting judgments vary somewhat with the groups compared. We discuss the role of metacognitive and normative processes in stereotype maintenance and stereotype change.
CRIS-Team Scopus Importer:2023-11-17
Keywords: comparative communication; fluency; norms; positivity; social acceptability; truth